PENERAPAN STRATEGI QUESTIONS STUDENT HAVE UNTUK MENINGKATKAN HASIL BELAJAR SUB TEMA PENGALAMAN BERSAMA TEMAN - Hutami, Witri (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
This research is motivated by the thematic learning process in Class I SDN Kembangarum 01 Semarang City still focuses on direct learning which is generally dominated by the teacher, students still passively accept what the teacher gives, generally only one way. learning outcomes in the sub-theme of experience with friends based on the results of daily tests, the value of learning completeness in the sub-theme of experience with friends with KKM 70 is only around 50% of the total number of first grade students at SDN Kembangarum 01 Semarang City, therefore strategies that can be applied to create active learning is a strategy of questions student have (questions from students). These problems are discussed through classroom action research which is carried out through 2 cycles with each cycle the stages are planning, action, observation and reflection. The results showed that: 1) The application of the question student have strategy in learning the sub-theme of experience with friends in class I SDN Kembangarum 01 Semarang City in the 2021/2022 academic year was carried out in four stages. 2) The learning outcomes of the sub-theme experience learning with friends after applying the questions student have strategy in class I SDN Kembangarum 01 Semarang City in the 2021/2022 academic year can be seen from the increase in the value of student learning outcomes where in the pre-cycle there are 15 students or 50%, the cycle In the first cycle there were 21 students, there were 70% and in the second cycle there were 26 students or 87%. Likewise, students' interest in learning also experienced an increase where in the first cycle there were 20 students or 67%, an increase in the second cycle, which was 28 students or 93%. This achievement is in accordance with the indicators of completeness and learning outcomes above 85%.